Propagation of Electromagnetic Wave into an Illuminated Polysilicon PV Cell - Vinci de Dieu Bokoyo Barandja; Bernard Zouma; Auguste Oscar Mackpayen; Martial Zoungrana; Issa Zerbo; Dieudonné Joseph Bathiebo (International Journal of Antennas and Propagation)
The increasing cohabitation between telecommunication antennas generating electromagnetic waves and solar panels poses the problem of interaction between these radio waves and solar cells. In order to study the effect of radio waves on the performance of a polycrystalline silicon solar cell in a three-dimensional approach, it is necessary to assess the attenuation of the radio wave in the illuminated polysilicon grain and also to find the expressions of its components. This work investigated the attenuation of radio waves into a polycrystalline silicon grain by analyzing, firstly, the behaviour of the penetration length of the radio waves into the polysilicon grain and secondly, the behaviour of the attenuation factor. The propagation of the radio waves into the polycrystalline silicon grain can be considered without attenuation that can be neglected.